2019
DOI: 10.1021/acs.jafc.9b03329
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Fate and Bioavailability of Glucosinolates in Kale (Brassica oleracea) Using Simulated Human Digestion and Caco-2 Cell Uptake Models

Abstract: Glucosinolates and their hydrolysis products were characterized in fresh and in in vitro gastric and intestinal digesta of Dinosaur kale (Brassica oleracea L var. palmifolia DC). In fresh kale, glucoraphanin, sinigrin, gluconapin, gluconasturtiin, glucoerucin, glucobrasscin, and 4-methoxylglucobrassicin were identified. After 120 min of gastric digestion, the levels of glucoraphanin, sinigrin, and gluconapin decreased, and no glucoerucin or glucobrasscin was detected. However, a concomitant increase in the glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
5
10
0
1
Order By: Relevance
“…Thus, the highest concentration of ITCs corresponded to red cabbage (4.41 mg/100 g fw), followed by red radish (0.86 mg/100 g fw) and broccoli (0.20 mg/100 g fw), while the concentration of ITCs in the intestinal digestates obtained from mustard sprouts was almost negligible. The specific extraction of ITCs from brassica foods during intestinal digestion fits well with previous studies [26,27]. These results make it possible to understand the actual contribution of each digestion stage (gastric and intestinal) to the intestinal concentration of ITCs during the whole gastrointestinal digestion process (Figure 3B).…”
Section: Influence Of Gastric Intestinal and Gastrointestinal Digestionsupporting
confidence: 88%
“…Thus, the highest concentration of ITCs corresponded to red cabbage (4.41 mg/100 g fw), followed by red radish (0.86 mg/100 g fw) and broccoli (0.20 mg/100 g fw), while the concentration of ITCs in the intestinal digestates obtained from mustard sprouts was almost negligible. The specific extraction of ITCs from brassica foods during intestinal digestion fits well with previous studies [26,27]. These results make it possible to understand the actual contribution of each digestion stage (gastric and intestinal) to the intestinal concentration of ITCs during the whole gastrointestinal digestion process (Figure 3B).…”
Section: Influence Of Gastric Intestinal and Gastrointestinal Digestionsupporting
confidence: 88%
“…In the tumor-only group, the average lung weight was 1:06 ± 0:06 g, whereas the TAP-nanoemulsion group suppressed the lung melanoma proliferation weights to 0:25 ± 0:05 g. There was no major difference in other organ weights among the three groups, suggesting that TAP-nanoemulsion had no significant toxic effects on these parts. Our previous study confirmed that AST restrained the formation of melanoma [15], and in this case, we also inhibited B16F10 cellular melanoma with lung metastases successfully.…”
Section: Tap-nanoemulsion Inhibits Lung Metastatic Melanomasupporting
confidence: 87%
“…ROS-sensitive fluorescent dye, 2′,7′-dichlorofluorescin diacetate (DCFDA) was used to determine PMA upregulated intracellular oxidative stress level in cells [ 15 ]. DCFDA is nonfluorescent, but in ROS presence (when reagent is oxidized), it shows green fluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…High gastrointestinal stability of sinigrin was also reported by other authors who investigated its stability after a simulated digestion process with commercial digestive enzymes [Kuljarachanan et al, 2020]. Hwang et al [2019] reported high stability of sinigrin in kale after gastric digestion with commercial digestive enzymes, but in contrast, the authors reported a low stability rate of sinigrin in kale after simulated duodenal digestive phase. This discrepancy can be explained by the effect of plant matrix on the duodenal stability of sinigrin and/or the differences between in vitro studies based on human and commercial digestive enzymes.…”
Section: In Vitro Digestion and Antioxidant Potential Of Sinigrin Loaded Liposomessupporting
confidence: 60%